Assessing Adoption Levels and Constraints to Modernized Rice Varieties Adoption by Rice Producers in Northern Ghana - Lamptey, C. Y.; Azumah, S. B.; Maanikuu, P. M. I. (Journal of Agricultural Studies, 2022)
The consumption of rice has increased dramatically in Ghana over the years. To enhance productivity in order to meet the demand of the commodity, some high-performing rice varieties have been disseminated to smallholder farmers in northern Ghana through a plethora of development interventions. Nevertheless, productivity is still low at farm gate compared to experimental stations, largely due to smallholders’ poor adoption of enhanced varieties and other socio-economic factors. Using primary data collected from 404 farmers, the study uses descriptive statistics to examine the adoption levels as well as reasons and challenges for adopting modernized rice varieties by producers in northern Ghana. The empirical results revealed low adoption levels of modernized rice varieties in the region; with Jasmine topping the list of most adopted (41.10%) followed by Agra (37.13%) and Afife (20.30%). The five most important reasons for farmer-use of modernized rice varieties in the region were: ready market for rice, ability of rice to withstand pest and disease attacks, higher consumer-demand, and pieces of advice from extension officers as well as advice by researchers to cultivate. High cost of production arising from input and labor costs coupled with high cost of farm credit are identified as major constraints to modernized rice varieties adoption in the region, and should be considered in any policy reforms or response by the government to address food insecurity issues within the context of current expected global food crises and to meet the sustainable development goals 1 and 2. Non-governmental and farmer-based organizations, and other actors in the rice value chain should collaborate with the government of Ghana to minimize the constraints and optimize adoption levels of modernized rice varieties in northern Ghana, which is a food basket of the country.